2017
DOI: 10.3847/1538-4357/835/2/123
|View full text |Cite
|
Sign up to set email alerts
|

Globular Clusters as Tracers of Fine Structure in the Dramatic Shell Galaxy NGC 474

Abstract: Globular clusters (GCs) are some of the most visible tracers of the merging and accretion history of galaxy halos. Metal-poor GCs, in particular, are thought to arrive in massive galaxies largely through dry, minor merging events, but it is rare to see a direct connection between GCs and visible stellar streams. NGC 474 is a post-merger early-type galaxy with dramatic fine structures made of concentric shells and radial streams that have been more clearly revealed by deep imaging. We present a study of GCs in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Using the galaxy mass-metallicity relation from Gallazzi et al (2005), the outer shell's mass-weighted metallicity of [Z/H]= −0.03 dex suggests that the disrupted galaxy had a stellar mass of log(M * /M ) ≥ 9.6. This estimate agrees well with the conclusion made by Lim et al (2017) that the disrupted galaxy is overmassive for a dwarf galaxy but still sub-L * . Kim et al (2012), using Spitzer imaging, already reported that the shells in NGC 474 are ∼6 − 10 percent as luminous as the underlying galaxy light (see their Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…Using the galaxy mass-metallicity relation from Gallazzi et al (2005), the outer shell's mass-weighted metallicity of [Z/H]= −0.03 dex suggests that the disrupted galaxy had a stellar mass of log(M * /M ) ≥ 9.6. This estimate agrees well with the conclusion made by Lim et al (2017) that the disrupted galaxy is overmassive for a dwarf galaxy but still sub-L * . Kim et al (2012), using Spitzer imaging, already reported that the shells in NGC 474 are ∼6 − 10 percent as luminous as the underlying galaxy light (see their Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…The number of galaxies that were counted in in these histograms and the total number of galaxies in the sample are noted in the corners. some collisional features for one system is presented in Lim et al (2017) and Fensch et al 2020 (submitted ). In principle, it will be possible to estimate the dynamical mass of the galaxies in our sample from the number of their GCs (e.g., Harris et al 2015;Forbes et al 2018) or kinematics (e.g., Samurović 2014;Bílek et al 2019b) after measuring the radial velocities of the GCs.…”
Section: The Matlas Surveymentioning
confidence: 99%
“…Keller et al 2012), and in external galaxies (e.g. Whitmore et al 1993;Lim et al 2017). Violent galaxy interactions such as major mergers are known to leave morphological signatures for as long as a few Gyr (∼ 2-3 Gyr for a major merger; e.g.…”
mentioning
confidence: 99%